Health Beliefs Concerning Breast Self-examination of Nurses in Turkey - Sevinc Tastan, RN, PhD; Emine Iyigün, RN, PhD; Ayse Kılıc, RN, PhD; Vesile Unver, RN, PhD (Elsevier, 2011)
Purpose: The purpose of the study was to evaluate the health beliefs regarding breast self-examination (BSE) and their relationship with age, educational status and history of breast cancer in the family among nurses working in a university hospital. Methods: A cross-sectional design was used, with a convenience sample of 381 nurses at a military university hospital in Ankara in Turkey. Data were collected by using a personal data form and the Champion's Health Belief Model Scale. Descriptive statistics, logistic regression, Mann-Whitney U test and Kruskal Wallis Test were conducted. Results: The proportion of nurses reported doing BSE regularly is 47.2%. Controlling variables such as age, body mass index, the age at first birth, breast cancer in the family history and educational background, we found that the subscales of the health belief model, BSE benefit (OR = 0.782), self-efficacy (OR = 0.919), and risk perception (OR = 0.114) have statistically significant effects on the risk of not making BSE. Conclusion: It is important to be aware of the health beliefs of nurses regarding BSE so that their own health can be protected and improved. Beneficial attitudes and behaviors of nurses regarding BSE will enable them to provide more effective services to women regarding breast cancer. Understanding the nurses' health beliefs, attitude and behavior that are influential to make BSE will guide nursing practices towards early diagnosis of breast cancer at the societal level.